Temperature Gradient-Dominated Electrical Behaviours in a Piezoelectric PN Junction - Guo, M.K.; Lu, Chunsheng; Qin, G.S.; Zhao, M.H. (SPRINGER, 2021)
© 2021, The Minerals, Metals & Materials Society. In this paper, we have systematically investigated the temperature gradient-dependent electrical behaviours in a piezoelectric PN junction. A new iterative computational method is proposed by utilizing the 1-D nonlinear theories of thermo-piezoelectric semiconductors. Coupling between the thermal gradient fields and polarization charges is discussed. It is found that the electromechanical field of a piezoelectric PN junction has a quick response to thermal gradient. Furthermore, gate voltage and carrier transport characteristics can be effectively tuned with thermal-induced and piezoelectric charges. It is shown that a piezoelectric PN junction is highly sensitive to the temperature gradient, which may provide an alternative approach to manipulate the carrier transport in piezotronic devices.